Structural Analysis of Reinforced Concrete Employee Dormitory on Soft Soil in Indramayu - Niken Adesti; Tira Roesdiana (Universitas Medan Area, 2026)
Employee dormitory buildings located in industrial areas require structural systems capable of resisting both gravity and seismic loads, particularly when constructed on soft soil that may amplify earthquake effects. This study aimed to evaluate the structural performance of a four-story reinforced concrete employee dormitory in Indramayu, Indonesia, under dead, live, and seismic loading in accordance with SNI 2847:2019 and SNI 1726:2019. A quantitative research design employing numerical simulation was adopted using ETABS software. Structural performance was assessed through the equivalent static seismic analysis by examining the natural period, base shear, inter-story drift, and reinforcement detailing of the reinforced concrete Special Moment Resisting Frame (SMRF). The analysis indicated that the calculated natural period satisfied the code requirements, the seismic base shear was appropriately distributed, and all inter-story drift values remained below the allowable limits. Furthermore, the column reinforcement detailing fulfilled the seismic ductility requirements specified in the Indonesian standards. These findings demonstrate that the proposed structural system provides adequate strength, stiffness, and stability for buildings constructed on soft soil. The study provides practical guidance for designing earthquake-resistant reinforced concrete buildings in soft-soil regions and contributes to improving structural safety in industrial residential facilities.